AKTIVITAS KEMILITERAN DI ANTARIKSA DALAM PERSPEKTIF HUKUM ANGKASA (ANGKATAN BERSENJATA ANTARIKSA AMERIKA): Military Activities in Space in the Perspective of Space Law (American Space Armed Forces) - Muhammad Alif Ramadhan; Ayu Nrangwesti (Reformasi Hukum Trisakti, 2024)
This research is motivated by the need to examine the legal justification for militarization in space and the process of forming the United States space military force in order to understand the related legal implications, because the legal basis and suitability are still questionable according to the principles of space law. The formulation of the problem of this article is How is the legality and process of forming the United States space military force with a focus on space law considerations related to militarization in space? The type of research used in writing this article is normative law and is analytically descriptive. The data used is secondary data and data collection is done through literature study, then conclusions are drawn through the deductive method. Data analysis is done by qualitative analysis method. The discussion includes the application of military aspects in outer space and the formation of military forces between the torture itself. The conclusion is formation of the United States Space Armed Forces is not prohibited long it is still in accordance with the ESD Charter and aims for world peace. But for military activities in outer space, this is prohibited, because not accordance with principles of space law.